Web-Based GIS for Safe Shipping in Istanbul Bosphorus Strait - Gumusay, Mustafa Umit (UNIV OSIJEK, TECH FAC, 2018)
The term shipping accident is mostly used to define any accident occurring at sea resulting in financial loss, including life or property or both. Common shipping accidents can be categorized into several groups: collision or contact, capsize, foundering, breaking-up, grounding, breakdown of the ship, underway, stranding and fire or explosion. Common shipping accidents in the strait of Istanbul are mostly collisions or stranding. Providing the necessary information for safe shipping in the strait could decrease shipping accidents. That kind of accurate information is generally achieved through navigation systems. Web-based GIS is one type which contributes to these navigation systems. Web-based GIS is a network-based tool that takes advantage of the internet, with the visualizing, analysing and accessing of distributed data and analysis functions. This study is aimed at creating a Web-based GIS application for effective coastal management, which includes berthing factors (anchorage areas, currents, submerged, etc.), maritime traffic factors (traffic separation schemes, traffic flow directions), closed areas and other factors (lighthouses, buoys, beacons, etc.) by digitizing printed navigation charts produced by the Turkish Naval Forces' Office of Navigation, Hydrography and Oceanography. Such an application could be widely used as it is web-based. The system is expected to contribute not only to the accurate navigation of high-tonnage ships but also to smaller vessels that do not have their own navigation systems.
Keywords: Bosphorus; Photograph; Shipping Accidents; Web-Based GIS; PREVENTION; Engineering